PWE-160 Prognostic significance of diagnostic delay in patients diagnosed with upper gastrointestinal tract cancer. (22nd June 2015) - Wheat, J; Blake, P; Karran, A; Lewis, WG
Abstract : Introduction: Recent public awareness campaigns for symptoms of cancer aim to improve outcomes by diagnosing cancer at an earlier stage. Whilst it is known that stage of disease at diagnosis predicts survival, the prognostic significance of delays in diagnosis and treatment of upper GI cancer is hitherto unknown. Method: A prospective study of 150 consecutive upper GI cancer patients [median age 70 yr, 96 male, 102 oesophageal, 48 gastric cancer] presenting to a UK cancer network was performed. Duration of symptoms prior to patient presentation, and times between referral, investigations, diagnosis, and treatment commencement were recorded. Deprivation scores were obtained from the Welsh Indices of Multiple Deprivation (WIMD). Outcome measures were whether potentially curative therapy was possible at time of decision to treat (DTT), and overall survival. Results: Median time from onset of symptoms to DTT was 18 weeks (3–143). There was no significant correlation between length of time from symptom onset to DDT and potentially curable disease (Chi 2 6.809, p = 0.146). There was no significant difference in overall survival according to length of time from onset of symptoms to DDT (Chi 2 4.209, p = 0.378). On multivariable analysis, gender (HR 3.600, 95% CI 1.659–7.811, p = 0.001) and overall deprivation rank (HR 1.001, 95% CI 1.000–1.001, p = 0.012) were significantly and independently associated with length of time from symptom onset to DDT. Conclusion: Whilst diagnostic and treatment delays can be lengthy, there is no significant overall effect on rates of potentially curable disease or survival. Disclosure of interest: None Declared.